Converging drivers of interpersonal violence: Findings from a qualitative study in post-hurricane Haiti. (March 2019) - Bermudez, Laura Gauer; Stark, Lindsay; Bennouna, Cyril; Jensen, Celina; Potts, Alina; Kaloga, Inah Fatoumata; Tilus, Ricardo; Buteau, Jean Emmanuel; Marsh, Mendy; Hoover, Anna; Williams, Megan Laughlin
Abstract: Objective: Interpersonal violence affecting women and children is increasingly recognized as a public health priority in humanitarian emergencies. Yet, research and intervention efforts have been fragmented across gender-based violence and child protection sectors. Using data from the Transforming Households: Reducing Incidence of Violence in Emergencies (THRIVE) project, this study sought to qualitatively investigate the intersecting drivers of multiple forms of violence in Côteaux, Haiti, while obtaining insight on how these drivers may be influenced by a humanitarian emergency. Methods: This analysis used transcripts obtained using a photo elicitation approach over the course of three sessions per person. Thirty-six individuals participated in the study: eight adult females, ten adult males, eight adolescent females, ten adolescent males. Participants were given cameras to capture images related to family relationships, family safety, and changes to family dynamics due to Hurricane Matthew and its aftermath. In subsequent sessions, these photographs were used as prompts for qualitative interviews. Results: Multiple and converging drivers of interpersonal violence were identified including the accumulation of daily stressors, loss of power/control, learned behavior (intergenerational cycle of abuse), and inequitable gender norms, all of which were influenced by the humanitarian context caused by Hurricane Matthew. Conclusions: Our findings suggest multiple and converging drivers of violence may be exacerbated in times of crises, requiring interdisciplinary responses. In order to comprehensively address the drivers of violence, practitioners and policy makers should consider the needs of individuals and their families holistically, integrating community-led, gender transformative efforts and positive parenting with basic needs provision.